Efektivitas Menggambar bagi Perkembangan Motorik Halus dan Psychological Well Being pada Anak Berkebutuhan Khusus: Penelitian - Della Putri Cherlya Utami; Angelica Cou; Nelda Rachel Manao; Hanna Christina Uranus (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effectiveness of drawing activities in improving fine motor skills and psychological well-being of children with special needs at Yayasan X, West Jakarta. The method used is qualitative descriptive, with data collected through weekly observations over one month and pre-test and post-test measurements of psychological well-being using a simple observation scale. The observed indicators include grip strength, movement accuracy, duration and quality of children's participation, as well as positive emotional expression, self-confidence, and social interaction. The results show gradual and consistent improvement in most participants in both fine motor skills and psychological well-being. In conclusion, drawing activities are effective in stimulating the development of fine motor skills and enhancing the psychological well-being of children with special needs, and are recommended for regular implementation in non-formal inclusive education.